Differences between the sexes in technical mastery of rhythmic gymnastics - Bozanic, A.; Miletic, D. (Journal of Sports Sciences, 2011)
The aims of this study were to determine possible differences between the sexes in specific rhythmic gymnastics techniques, and to examine the influence of various aspects of technique on rhythmic composition performance. Seventy-five students aged 21 ± 2 years (45 males, 30 female) undertook four test sessions to determine: coefficients of asymmetry, stability, versatility, and the two rhythmic compositions (without apparatus and with rope). An independent-sample t-test revealed sex-based differences in technique acquisition: stability for ball (P < 0.05; effect size = 0.65) and club (P < 0.05; effect size = 0.79) performance and rhythmic composition without apparatus (P < 0.05; effect size = 0.66). Multiple regression analysis revealed that the variables for assessing stability (beta = 0.44; P < 0.05) and versatility (beta = 0.61; P < 0.05) explained 61% of the variance in the rhythmic composition performance of females, and the variables for assessing asymmetry (beta =-0.38; P < 0.05), versatility (beta = 0.32; P < 0.05), and stability (beta = 0.29; P < 0.05) explained 52% of the variance in the rhythmic composition performance of males. The results suggest that female students dominate in body skill technique, while male students have the advantage with apparatus. There was a lack of an expressive aesthetic component in performance for males. The need for ambidexterity should be considered in the planning of training programmes.